PERANCANGAN ULANG BLANKING DIES DENGAN DOUBLE PUNCH UNTUKPRODUK CHAIN PULLER SEPEDA MOTOR YAMAHA VEGA R - Waluyo, Joko; Purwanto, Adi; Simamora, Riandy Debataraja (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
The increasing of Indonesia society necessity of automotive product, especially motorcycle, claiming automotive producer to more productive in yielding it’s product. One of way to increase it’s product is by modified the production process to become more efficient in using working time and keep the quality of the product is good. Chain puller is one of Yamaha Vega R motorcycle component, that made with stamping process using press machine. To make one product of chain puller is needed eight process that is shearing, blanking, swaging, bending, piercing-cutting, cheaser, buffing-chamfering and threading. In this script the process to be studied is blanking process. In chain puller production process can only produce one blank product in one stroke of press machine. starting from the chain puller drawing part that will be produce by Yamaha Motor company. Some data like product dimension, product materials using SPHC ad finishing process, can getting from that drawing. From that data we can getting the tensile strength of SPHC is 270 N/mm2 and slice circumference is 382,742 m. Then we can calculate another data that needed to design the dies and we getting slice force is 26964,63 kgf, stripper force is 2696,463 kgf, total force is 30 ton, clearance is 0,155 m, die freedom using angular clearance with straight slice side with h= 10 mm and α = 2°, high of penetration is 3,3 mm. By using two punch on the blanking dies, in every stroke of press machine can produced two blank product all at once.